2013
DOI: 10.1002/etc.2369
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil pH on the toxicity of zinc oxide nanoparticles to the terrestrial isopod Porcellionides pruinosus

Abstract: concentrations increased in a dose-related manner, but no effect of soil pH was found. It is suggested not only that dissolved or free Zn in porewater contributed to uptake and toxicity, but also that oral uptake (i.e., ingestion of soil particles) could be an important additional route of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…As previously stated, the use of terrestrial isopods in ecotoxicology is not new and considerable work has been already described, including different procedures and test durations, established for evaluating different endpoints (Loureiro et al, 2002(Loureiro et al, , 2006Santos et al, 2010;Calhôa et al, 2012;Morgado et al, 2013;Tourinho et al, 2013). Despite the duration required to evaluate different live trait parameters, the use of long term exposures are not frequently applied (Ferreira et al, 2015), although they are advisable if a more detailed and comprehensive effects of a stressor is aimed.…”
Section: Introductionmentioning
confidence: 95%
“…As previously stated, the use of terrestrial isopods in ecotoxicology is not new and considerable work has been already described, including different procedures and test durations, established for evaluating different endpoints (Loureiro et al, 2002(Loureiro et al, , 2006Santos et al, 2010;Calhôa et al, 2012;Morgado et al, 2013;Tourinho et al, 2013). Despite the duration required to evaluate different live trait parameters, the use of long term exposures are not frequently applied (Ferreira et al, 2015), although they are advisable if a more detailed and comprehensive effects of a stressor is aimed.…”
Section: Introductionmentioning
confidence: 95%
“…Only two studies have evaluated the effects of soil exposure on isopods for ZnO and CeO 2 -NPs (Tourinho et al, 2013(Tourinho et al, , 2015. Previous studies with the isopod Porcellionides pruinosus have shown that different routes of exposure (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The feeding activity of soil fauna can be significantly boosted with liming the soil [34]. The feed consumption ratio in isopods (Porcellionides pruinosus) was higher at soil pH 7.3 as compared to soil pH 6.2 and 4.5 [35].…”
Section: Discussionmentioning
confidence: 99%